CASTRATION AS AN ENTERPRISE OF CRIMINAL POLICY IN THE CHILD PROTECTION LAW - Abdul Kadir; Dwi Nur Fauziah Ahmad (Universitas Muhammadiyah Tangerang, 2020)
The rise of sexual violence against children in Indonesia requires strict legal rules and a deterrent effect on perpetrators. So the government in the latest child protection law includes punishment for castration. The issues raised are how the application of criminal law against perpetrators of sexual violence against children (pedophilia) in Indonesia and how the additional criminal regulation of castration as a criminal law policy in the child protection law. The type of research used is normative research, which is research that focuses on a positive direction in the form of statutory regulations. Criminal application for perpetrators of sexual violence against children is regulated in the Criminal Code and the Child Protection Act. Castration is a new legal policy by the government in dealing with the perpetrators of sexual violence against children.Keywords: Castration, Legal Policy, Child Protection